Protein for Preterm Infants: How Much is Needed? How Much is Enough? How Much is Too Much? - William W. Hay; Patti Thureen (Elsevier, 2010)
Preterm infants require considerably more protein to achieve normal intrauterine growth rates than is commonly fed to them during their first postnatal days. Continuing protein nutrition to maintain normal growth rates often is not achieved until several weeks after birth. Most very preterm infants do not receive the protein necessary to produce the 2-3 kilograms of body mass over a 12-16 week period of NICU care and, as a result, end up growth restricted by term, in lean body mass more than fat. This article reviews the requirements for protein and amino acids necessary to achieve normal growth and development of preterm infants. Protein requirements at 24-30 weeks' gestation are as high as 4 g/kg/day, decreasing to 2-3 g/kg/day by term. Individual amino acids are important not just as building blocks for protein synthesis and net protein balance, but also as essential signalling molecules for normal cellular function. Perhaps most importantly, brain growth and later life cognitive function are directly related to protein intake during the neonatal period in preterm infants. Data are reviewed that document successful increase in protein balance in preterm infants achieved with higher than usual rates of amino acid and protein nutrition, noting that positive protein balance requires at least 1.5 g/kg/day, but there still is increased protein balance up to 4 g/kg/day. Further research is necessary to determine optimal amounts and mixtures of protein and amino acids for both intravenous and enteral feeding to improve growth, development, and functional capacity of preterm infants.